PENGARUH LINGKUNGAN KELUARGA BAHAGIA TERHADAP AKHLAK ANAK - Solihat, Annisa; Ulum, Moh Saeful (THORIQOTUNA: Jurnal Pendidikan Islam, 2020)
This study aims to determine the effect of a Happy Family Environment on the Moral of Children in Madrasah Diniyah Al-Ikhlash, Pakemitan Kidul Village, Ciawi District, Tasikmalaya Regency. The method used in this research is a descriptive method with a quantitative approach, namely research in the form of expressing the current conditions by considering past conditions through processing the numbers obtained in the study. Based on the results of this study, it can be concluded that children's morals can be improved through a Happy Family Environment. It is recommended that every family member, especially parents, to be more able to improve and create a good and happy family environment so that children's morals can be better.